Toxicity Test of Arbenan (Duchesnea indica (Jacks.) Focke) Leaf Ethanolic Extract Using the Brine Shrimp Lethality Test (BSLT) Method - Nurfadhillah, Andi Zahra (UNIVERSITAS MUSLIM INDONESIA, 2024)
Arbenan (Duchesnea indica (Jacks.) Focke) is a plant that has various benefits. The toxic potential of arbenan leaves is known through a toxicity test using the Brine Shrimp Lethality Test (BSLT) method. The purpose of this study was to investigale the toxicity of arbenan leaves (Duchesnea indica (Jacks.) Focke) to Artemia salina Leach larvae, and to determine the LC50 value. Arbenan leaves were extracted by maceration using 70% ethanol solvent. Then a phytochemical screening was carried out which showed the chemical content in arbenan leaves, namely tannins, flavonoids, and saponins. Toxicity testing of arbenan leaf extract against Artemia salina Leach larvae used concentration variations of 250 ppm, 300 ppm, 350 ppm, and 400 ppm. Then observed after 24 hours to see the death of Artemia salina Leach larvae. The results of the research can be seen through probit analysis by calculating the LC50 value of arbenan leaf extract is 323,593 (toxic).